A Versatile Compact Parahydrogen Membrane Reactor. Issue 24 (26th October 2021) - TomHon, Patrick M.; Han, Suyong; Lehmkuhl, Sören; Appelt, Stephan; Chekmenev, Eduard Y.; Abolhasani, Milad; Theis, Thomas
Abstract: We introduce a Spin Transfer Automated Reactor (STAR) that produces continuous parahydrogen induced polarization (PHIP), which is stable for hours to days. We use the PHIP variant called signal amplification by reversible exchange (SABRE), which is particularly well suited to produce continuous hyperpolarization. The STAR is operated in conjunction with benchtop (1.1 T) and high field (9.4 T) NMR magnets, highlighting the versatility of this system to operate with any NMR or MRI system. The STAR uses semipermeable membranes to efficiently deliver parahydrogen into solutions at nano to milli Tesla fields, which enables 1 H, 13 C, and 15 N hyperpolarization on a large range of substrates including drugs and metabolites. The unique features of the STAR are leveraged for important applications, including continuous hyperpolarization of metabolites, desirable for examining steady‐state metabolism in vivo, as well as for continuous RASER signals suitable for the investigation of new physics. Abstract : New STAR : The spin transfer automated reactor (STAR) system is a next‐generation continuous microfluidic system for generation of hyperpolarized substrates with parahydrogen‐based chemistry. In the present work, we demonstrate continuous production of hyperpolarized biomedically relevant compounds (pyruvate and metronidazole) and push the boundaries of new parahydrogen‐driven RASER physics with continuous pumping of a hyperpolarized solution.